Continuous thermosalinograph oceanography along RV SONNE cruise SO279 - Aaron Beck; Michael Schlundt (PANGAEA, 2022)
Underway temperature and salinity data was collected along the cruise track with two autonomous measurement systems, called self-cleaning monitoring boxes (SMBs). Usually, the SMBs are changed after 12 hours. While temperature is taken at the water inlet in about 4 m depth, salinity is estimated within the SMB from conductivity and interior temperature. No calibration was performed, neither for temperature nor for salinity. For details to all processing steps see Data Processing Report.